Essentials of managing treasury - Horcher, Karen A. (Hoboken, N.J. : John Wiley & Sons, Inc., 2006)
This book describes each functional area within treasury and includes guidelines for best practices and relevant technologies.With tips and techniques, it provides a practical overview of treasury and its relationship to every part of an organization.
Includes index.
aia 30/05/13
Loans
Keywords: Cash management; Finance